The effects of English language for communication towards student’s proficiency level / Mohd Noor Azmin Hashim - Hashim, Mohd Noor Azmin (2010)
This research was conducted to analyze form four students of SMK Tun Mutahir on the effects of English language for communication towards students’ proficiency level. A total of 30 students were involved as respondents, in which they were required to complete a questionnaire and has given a small picture on the scenario regarding the use of English among secondary students and the effects of it on their proficiency level. The research findings showed that most of the students are aware of the importance of acquiring and mastering the language and one way is to practice to use the language through communication.